ANALYSIS OF VALUE CREATION: PRODUCT INNOVATION, PRODUCT DEVELOPMENT AND PRODUCT QUALITY TO COMPETITIVE ADVANTAGE - Hendratmoko, Suseno (The journal of contemporary issues in business and government, 2021)
The dynamics of the business environment in the midst of the Covid19 pandemic since few months ago until now has made business people think more creatively so that their business activities can survive. Through innovation, product development, and improvement of prime product quality, it is hoped that it can create a competitive advantage compared to other similar products. From the research conducted on the object of research, Bakpia kukus brand Tugu Yogyakarta, obtained results from 150 respondents using random sampling techniques as follows: (1) the influence of product innovation variables has a positive and significant effect on competitive advantage; (2) product development variables have a positive and significant effect on competitive advantage; and (3) product quality variables also have a positive effect on competitive advantage. Then it is necessary to add also based on the research results also obtained that simultaneously, the variable innovation, product development and quality have a positive and significant effect on the competitive advantage of steamed bakpia products with the Tugu brand of Yogyakarta.